Zwierząt obraz Pindarowy - Pawlak, Kamil (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
The article discusses the image of animals in epinicia by Pindar (ca. 518 – ca. 438 BC ). It also draws attention to the relationship between man and animal in the poet’s work. The author presents a typology of different functions that animals perform in triumphant songs by the poet. A picture of the animal, as an integral part of the human world, emerges in the course of the analysis. This way of thinking about the world of animals and people becomes universal also for subsequent and contemporary literature. The article deals also with the objective and subjective images of the animal which were created by Pindar in his odes. The analysis attempts to answer the question about the purpose of animal comparisons used by Pindar in relation to man.
Keywords: Pindar; choral poetry; animals; ancient Greeks